2021
DOI: 10.3390/ijerph18010326
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impact of Endodontic Therapy on Survival among Dialysis Patients in Taiwan: A Nationwide Population-Based Cohort Study

Abstract: Objectives Dental problems occur widely in patients with chronic kidney disease (CKD) and may increase comorbidities. Root canal therapy (RCT) is a common procedure for advanced decayed caries with pulp inflammation and root canals. However, end-stage renal disease (ESRD) patients are considered to have a higher risk of potentially life-threatening infections after treatment and might fail to receive satisfactory dental care such as RCT. We investigated whether appropriate intervention for dental problems had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Another prospective cohort study found untreated caries to increase all-cause mortality in HD patients [ 10 ]. A Taiwanese nationwide population-based cohort study in patients with CKD showed that sufficient root canal treatment, which is often needed in case of fairly advanced carious lesions, leads to a lower risk of death during HD therapy [ 55 ]. In the included studies, therapy-related issues (e.g., eGFR) or inflammatory laboratory values (e.g., C-reactive protein [CRP]) were rarely considered across investigations, making a conclusion on this issue impossible.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective cohort study found untreated caries to increase all-cause mortality in HD patients [ 10 ]. A Taiwanese nationwide population-based cohort study in patients with CKD showed that sufficient root canal treatment, which is often needed in case of fairly advanced carious lesions, leads to a lower risk of death during HD therapy [ 55 ]. In the included studies, therapy-related issues (e.g., eGFR) or inflammatory laboratory values (e.g., C-reactive protein [CRP]) were rarely considered across investigations, making a conclusion on this issue impossible.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, timely access to endodontic treatment can considerably impact upon the lives of CKD patients in a positive way. Studies conducted in Taiwan using real-world population-based data have documented improved survival in CKD patients undergoing dialysis when timely root canal treatment was undertaken ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Com base nos resultados e nos artigos incluídos no presente trabalho, sobre as manifestações bucais que incluem: cárie, perda de inserção clínica, doença periodontal, fluorose, cálculo dental, placa bacteriana, inflamação perirradicular, infecção microbiana no sistema de canais radiculares, disgeusia, hálito urêmico, xerostomia, hipoplasia de esmalte e distúrbios gustativos (Parkar;Ajithkrishna, 2012;Tiwari et al, 2013;Swapna;Koppolu;Prince, 2017;Nascimento et al, 2018;Misaki et al, 2019;Sharma et al, 2020;Chiu et al, 2021).…”
Section: Discussionunclassified
“…O tratamento para DRC inclui o uso de medicamentos anti-hipertensivos e a baixa ingestão de líquidos, em consequência disso, pode-se ocorrer desidratação e em função desse fato a xerostomia pode se tornar um sintoma frequente e persistente nesses pacientes (Howell;Perry;Patel, 2016;Nascimento et al, 2018;Marinosk et al, 2019;Chiu et al, 2021) 2019) em suas pesquisas notaram que a relação da cárie com o paciente renal crônico é menor que no grupo saudável. Foram sugeridas algumas explicações para esse fato, dentre elas, o alto índice de uréia que afeta o pH bucal, uma maior quantidade de fosfato e uma baixa quantia de cálcio, afetando sua ação no processo de desmineralização e remineralização, consequentemente, aumentando a capacidade tampão exercida pela saliva, assim a doença cárie não terá uma instalação facilitada em comparação aos pacientes saudáveis (Gautam et al, 2014;Tadakamadla et al, 2014;Fregoneze et al, 2015;Swapna;Koppolu;Prince, 2017;Pham;Lee, 2018;Menezes et al, 2019;Silva et al, 2019).…”
Section: Discussionunclassified